Authority of Women’s Bodies in Nengget Tanah Karo Ritual: a Study of Root of Violence against Women - Brahmana, Lorensia (Jurnal Perempuan, 2015)
This writing discuss women’s body authority in Nengget Ceremony in Karo Land that attacked by the disaster of Sinabung Mountain eruption. The patriarkal construction in the traditional custom and culture as well the religion interpretation has become the tool which has contributed to legalize the woman’s oppression in Karo Regency. This writing will discuss how the patriarkal domination in the traditional marriage was built through traditional relation model which legitimated the concept of man absolute ownership over women’s property, status, role, and body. This writing will discuss the influence of the relation model of violence in family.